The Relationship between Self-Confidence and Social Support of Badminton Athletes in the Training Phase - Dewi, Berliana Mutiara; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Indonesian Journal of Sport Management, 2025)
Background: Self-belief and social support are critical factors in the performance of badminton athletes, but research on their relationship in the training phase is limited. Purpose: This study aims to analyze the relationship between self-efficacy and social support in badminton athletes during the training phase. Methods: Descriptive quantitative research with 32 UPI athletes using the Trait Sport-Confidence Inventory (TSCI) and Multidimensional Scale of Perceived Social Support (MSPSS). Data analysis used descriptive statistics and the Spearman correlation test. Results: There was a significant positive relationship between social support and confidence of badminton athletes in the training phase. Conclusion: Social support plays an important role in improving athletes' self-efficacy. Practical recommendations include strengthening social support by coaches and mental training by athletes. Implications and Recommendation: Further research can use a larger sample and include other variables such as intrinsic motivation competing experience or coach leadership style.